Hybrid Biocomposites Based on Used Coffee Grounds and Epoxy Resin: Mechanical Properties and Fire Resistance - Tuan Anh Nguyen; Quang Tung Nguyen (International Journal of Chemical Engineering)
Studies on using biomaterials hybridized with other materials to produce biomaterials have been paid more attention due to their low cost, abundance, renewability, and degradability. Therefore, these materials are ecofriendly and nontoxic to humans. A large number of used coffee grounds (SCGs) are often discarded and replacements are necessary for dealing with environmental problems. This work developed sustainable materials by reusing SCGs. Used coffee grounds were mixed with epoxy resin at different amounts: 30 wt %, 40 wt %, 50 wt %, and 60 wt %. SCGs were treated with 0.5 N NaOH, at SCGs/NaOH ratio of 1 : 2. SEM images showed that the material with 30 wt % SCGs has good compatibility without phase division on the SCGs-epoxy interface. Results of mechanical properties of epoxy composites with 30 wt % SCGs are as follows: tensile strength of 44.81 ± 10 MPa, flexural strength of 80.07 ± 0.16 MPa, compressive strength of 112.56 ± 0.11 MPa, and Izod strength and impact of 8.21 ± 0.19 kJ/m2. In terms of flame-retardant properties, the oxygen index is limited to 20.8% ± 0.20 and the burning rate according to UL94HB is 27.02 ± 0.29 mm/min. The obtained results indicate that it is possible to produce biohybrid composites from epoxy resin and SCGs. This work offers an ecofriendly alternative method to use the waste of the coffee industry. It contributes to improvements of the general characteristics of composites such as mechanical, thermal, and flame-retardant properties. This work proved that SCGs have a high potential to be used in a wide range of composite materials for civil engineering applications.